The Bilaterian Head Patterning Gene six3/6 Controls Aboral Domain Development in a Cnidarian - Sinigaglia, Chiara (Public Library of Science, 2013)
The origin of the bilaterian head is a fundamental question for the evolution of animal body plans. The head of bilaterians develops at the anterior end of their primary body axis and is the site where the brain is located. Cnidarians, the sister group to bilaterians, lack brain-like structures and it is not clear whether the oral, the aboral, or none of the ends of the cnidarian primary body axis corresponds to the anterior domain of bilaterians. In order to understand the evolutionary origin of head development, we analysed the function of conserved genetic regulators of bilaterian anterior development in the sea anemone Nematostella vectensis. We show that orthologs of the bilaterian anterior developmental genes six3/6, foxQ2, and irx have dynamic expression patterns in the aboral region of Nematostella. Functional analyses reveal that NvSix3/6 acts upstream of NvFoxQ2a as a key regulator of the development of a broad aboral territory in Nematostella. NvSix3/6 initiates an autoregulatory feedback loop involving positive and negative regulators of FGF signalling, which subsequently results in the downregulation of NvSix3/6 and NvFoxQ2a in a small domain at the aboral pole, from which the apical organ develops. We show that signalling by NvFGFa1 is specifically required for the development of the apical organ, whereas NvSix3/6 has an earlier and broader function in the specification of the aboral territory. Our functional and gene expression data suggest that the head-forming region of bilaterians is derived from the aboral domain of the cnidarian-bilaterian ancestor.